Pengaruh Penggunaan Aplikasi “Bumil Bahagia” Berbasis Android terhadap Tingkat Pengetahuan Faktor Risiko PEAD pada Ibu Hamil di Kabupaten Banyumas - Mulhamatus Latifatus Suri; Wilis Dwi Pangesti (Jurnal Kebidanan Harapan Ibu Pekalongan, 2024)
Preeclampsia is one of the biggest problems in pregnancy and is a cause of infant and maternal death every year in the world. The low knowledge of pregnant women is one of the factors in recognizing the condition of their pregnancy. The use of digital health brings a lot of medical information exchange between patients and health workers, health services in the context of differential diagnosis, access to health is more efficient and cost effective. This study aims to determine the effect of using the android-based "pregnant mother happy" application on the level of knowledge of PEAD risk factors in pregnant women in Banyumas district. Pre-experimental design research. Sempel used the cluster sampling approach for pregnant women aged 20-34 weeks' gestation. The results of the Wilcoxon test with a p value <0.001, before being given the intervention the knowledge of pregnant women was in the good category (51.9%), after being given the intervention it increased (66.7%). There is an effect of the use of the Android-based “happy pregnant woman” application on the level of knowledge of PEAD risk factors in pregnant women in Banyumas district in 2023.